Reversible Hydrogenase Activity Confers Flexibility to Balance Intracellular Redox in Moorella thermoacetica - Kobayashi, Shunsuke; Kato, Junya; Wada, Keisuke; Takemura, Kaisei; Kato, Setsu; Fujii, Tatsuya; Iwasaki, Yuki; Aoi, Yoshiteru; Morita, Tomotake; Matsushika, Akinori; Murakami, Katsuji; Nakashimada, Yutaka (Frontiers in Microbiology, 2022)
Hydrogen (H2) converted to reducing equivalents is used by acetogens to fix and metabolize carbon dioxide (CO2) to acetate. Utilization of H2 enables not only autotrophic growth, but also mixotrophic metabolism in acetogens, enhancing carbon utilization. This feature seems useful, especially when the carbon utilization efficiency of organic carbon sources is lowered by metabolic engineering to produce reduced chemicals, such as ethanol. The potential advantage was tested using engineered strains of Moorella thermoacetica that produce ethanol. By adding H2 to the fructose-supplied culture, the engineered strains produced increased levels of acetate, and a slight increase in ethanol was observed. Utilization of a knockout strain of the major acetate production pathway, aimed at increasing the carbon flux to ethanol, was unexpectedly hindered by H2-mediated growth inhibition in a dose-dependent manner. Metabolomic analysis showed a significant increase in intracellular NADH levels due to H2 in the ethanol-producing strain. Higher NADH level was shown to be the cause of growth inhibition because the decrease in NADH level by dimethyl sulfoxide (DMSO) reduction recovered the growth. When H2 was not supplemented, the intracellular NADH level was balanced by the reversible electron transfer from NADH oxidation to H2 production in the ethanol-producing strain. Therefore, reversible hydrogenase activity confers the ability and flexibility to balance the intracellular redox state of M. thermoacetica. Tuning of the redox balance is required in order to benefit from H2-supplemented mixotrophy, which was confirmed by engineering to produce acetone.